Retraction: In vivo potentiation of human oestrogen receptor α by Cdk7‐mediated phosphorylation. (December 2013) - Ito, Saya; Takeyama, Ken‐ichi; Yamamoto, Ayako; Sawatsubashi, Shun; Shirode, Yuko; Kouzmenko, Alexander; Tabata, Tetsuya; Kato, Shigeaki
<x xml:space="preserve">Abstract</x> Retraction: The above article in Genes to Cells (doi: 10.1111/j.1365‐2443.2004.00777.x ), published online on 6 October 2004 in Wiley Online Library (http://onlinelibrary.wiley.com/), has been retracted by agreement between the authors, the journal Editor in Chief, Mitsuhiro Yanagida, and Wiley Publishing Asia Pty Ltd. The retraction has been agreed to due to multiple usage of the tissue images in Figures 1(B), 2, 3(C), 4 and 6, and the absence of the gel image for the lane 5 of 'GFP' in Figure 1(B).